MALDI-imaging analyses of honeybee brains exposed to a neonicotinoid insecticide - Catae, Aline F [UNESP]; da Silva Menegasso, Anally R [UNESP]; Pratavieira, Marcel [UNESP]; Palma, Mario S [UNESP]; Malaspina, Osmar [UNESP]; Roat, Thaisa C [UNESP] (Wiley, 2019)
BACKGROUND: Toxicological studies evaluating the possible harmful effects of pesticides on bees are important and allow the emergence of protection and pollinator conservation strategies. This study aimed to evaluate the effects of exposure to a sublethal concentration of imidacloprid (LC 50/100 : 0.014651 ng imidacloprid µL −1 diet) on the distribution of certain proteins identified in the brain of Apis mellifera worker bees using a MALDI-imaging approach. This technique enables proteomic analysis of tissues in situ by monitoring the spatiotemporal dynamics of the biochemical processes occurring at a specific time in specific brain neuropils. For this purpose, foraging bees were exposed to an 8-day diet containing a sublethal concentration of imidacloprid corresponding to the LC 50/100 . Bees were collected on day 8 of exposure, and their brains analyzed using protein density maps. RESULTS: The results showed that exposure to imidacloprid led to a series of biochemical changes, including alterations in synapse regulation, apoptosis regulation and oxidative stress, which may adversely impair the physiology of these colony bees. CONCLUSION: Worker bee contact with even tiny amounts of imidacloprid had potent effects leading to the overexpression of a series of proteins related to important cellular processes that were possibly damaged by the insecticide. © 2018 Society of Chemical Industry.
Keywords: Apis mellifera; apoptosis; ecotoxicology; imidacloprid; oxidative stress; synapse